Exploration of Catalytic Activity of Trypsin for C(sp3)‐H Functionalization and Consequent C‐C Bond Formation. Issue 17 (2nd May 2019) - Shukla, Ratnakar Dutt; Rai, Byanju; Kumar, Atul
Abstract : Employment of trypsin for C(sp 3 )‐H functionalization to construct a new C‐C bond utilizing 2‐methylbenzothiazole/2‐methyl benzoxazole with diones has been explored. This novel and greener approach have been effectively utilized to afford bioactive 3‐substituted‐3‐Hydroxy‐2‐oxindoles. Furthermore, the presented method combines the enzyme promiscuity and C‐H functionalization which open up and expands the repertoire of chemoenzymatic C‐H functionalization. Abstract : The catalytic promiscuity of trypsin from porcine pancreas for the C(sp 3 )‐H functionalization 2‐methylbenzothiazole/2‐methyl benzoxazole with diones to construct a new C‐C bond was discovered. Broad substrate specificity was tested; and the developed protocol has also been effectively utilized for the synthesis of bioactive 3‐substituted‐3‐Hydroxy‐2‐oxindoles. Furthermore, this novel and green method combines the enzyme promiscuity and C‐H functionalization which open up and expands the repertoire of chemoenzymatic C‐H functionalization.